Comparative studies on the genetic, antigenic and pathogenic characteristics of Bokeloh bat lyssavirus - Nolden, Tobias; Banyard, A.C.; Finke, Stefan; Fooks, A.R.; Hanke, Dennis; Höper, Dirk; Horton, D.; Mettenleiter, Thomas C.; Müller, Thomas; Teifke, Jens Peter; Freuling, Conrad Martin (Journal of General Virology, 2014)
Bokeloh bat lyssavirus (BBLV), a novel lyssavirus was isolated from a Natterer's bat (Myotis nattererii), a chiropteran species with a widespread and abundant distribution across Europe. As a novel lyssavirus, the risks of BBLV to animal and human health are unknown and as such characterization both in vitro and in vivo was required to assess pathogenicity and vaccine protection. Full genome sequence analysis and antigenic cartography demonstrated that the German BBLV isolates are most closely related to EBLV-2 and Khujand virus and can be characterised within phylogroup I. In vivocharacterization demonstrated that BBLV was pathogenic in mice when inoculated peripherally causing clinical signs typical for rabies encephalitis, with higher pathogenicity observed in juvenile mice. A limited vaccination challenge experiment in mice was conducted and suggested that current vaccines would afford some protection against BBLV although further studies are warranted to determine a serological cut off for protection.